Factors influencing inclusive teachers’ acceptance to adopt eLearning platforms in classroom: a case study in Oman - Almaki, Samah Hatem; Al Mazrouei, Ahmed Khalaf; Mafarja, Nofouz; Naseem, Warda; Sial, Muhammad Adnan; Naveed, Rana Tahir (Frontiers in Education, 2024)
COVID-19 has sparked a significant shift in education toward the use of eLearning platforms. Inclusive teachers encounter several challenges when adopting eLearning platforms for education. The purpose of this study was to examine factors influencing inclusive teachers' acceptance of eLearning platforms according to the unified theory of acceptance and use of technology (UTAUT2) model. Overall, 128Omanis inclusive teachers completed the survey questionnaire. The findings revealed the general acceptability of eLearning platforms. Higher performance expectancy, facilitating conditions, social influence, and service quality were all significant predictors of the eLearning platform on behavioral intention. Moreover, the findings showed that further support and training are needed for inclusive teachers to use eLearning systems.